HPLC-MS and MSMS analysis of 2-methoxy alkylglycerols isolated from shark liver oil - Aðalheiður Dóra Albertsdóttir 1984- (2011)
The 1-O-alkyl-sn-glycerols, also known as glyceryl ethers, occur widely in Nature, but in particularly high amounts in the liver oil of various cartilaginous fish including shark species. Shark liver oil has been used in Scandinavia for centuries for its various remedial effects that have been attributed to the glyceryl ethers. Minor parts (2 - 4 %) of the glyceryl ether fraction of such oils are substituted with a methoxyl group located at the 2-position of the alkyl moiety. Such methoxylated ether lipids (1-O-(2’-methoxyalkyl)-sn-glycerols) are interesting compounds that have been claimed to offer various bioactivities including antifungal, antibacterial and antitumor properties. The objective of this work was to develop a HPLC- MS analytical method to investigate a mixture of such 2-methoxy alkylglycerols (MAGs) isolated from the liver oil of deep sea sharks originating in the North Atlantic Ocean. The work was focused on the ammonium and lithium adducts of the MAGs. Seven MAG adducts were found to account for the majority of the signals in the HPLC-MS analyses and accurate mass values were acquired for all of them. These compounds constitute two saturated (C16:0 and C18:0), three monounsaturated (C16:1 and two C18:1 isomers) and two polyunsaturated (C18:3 and C22:6) MAG derivatives. Confirmation of the MAGs general framework was achieved by analyzing the ammonium adduct MSMS spectra while the lithium MSMS spectra provided information regarding the location of the double bonds in the mono- and polyunsaturated MAGs. Icelandic Research Fund